COMPARATIVE ANALYSIS OF NUMERICAL METHODS OF DETERMINATION OF PARAMETERS OF BINARY STARS. CASE OF SPHERICAL COMPONENTS - Andronov, I. A.; Tkachenko, M. G. (Одеські астрономічні публікації, 2013)
We discuss methods for modeling eclipsing binary stars. There are few realizations of the Wilson- Devinney (1971) code and its improvements, e.g. “Binary Makef’, “Phoebe”. A parameter search using the Monte- Carlo method was realized by Zola et al. (2010), which is efficient in expense of too many evaluations of the test function. We compare existing algorithms of minimization of multi-parametric functions. To study methods, we adopt a simplified model of an eclipsing binary at a circular orbit assuming spherical components with an uniform brightness distribution. This model resembles more advanced models in a sense of correlated parameter estimates due to a similar topology of the test function. Such a model may be applied to detached Algol-type systems, where the tidal distortion of components is negligible.